Common characteristics of feedstock stage in life cycle assessments of agricultural residue-based biofuels. (1st October 2019) - Wang, Zhiwei; Lei, Tingzhou; Yan, Xiaoyu; Chen, Gaofeng; Xin, Xiaofei; Yang, Miao; Guan, Qian; He, Xiaofeng; Gupta, Ashwani K.
Graphical abstract: Highlights: The field-to-fuel life cycle of agricultural residue-based biofuels was divided. Common characteristics of production and collection of agri-residues were analyzed. LCA allocations with agri-residues-to-grain weight and price ratios were summarized. Benefits of direct emissions reduction during the feedstock stage were discussed. Abstract: In this study, we conducted life cycle assessments (LCAs) for fuels based on different types of agricultural residues and determined the characteristics common to all LCAs. Each fuel type required specific conversion technology during the feedstock stage, particularly during the production and collection processes. We divided the field-to-fuel life cycle into five high-level and relatively independent sub-stages: production of agricultural residues, collection of agricultural residues, conversion of agricultural residues to biofuels, biofuel distribution, and biofuel utilization. We then illustrated the common characteristics during the feedstock stage for the first two field-to-fuel life cycle sub-stages: production and collection of agricultural residues. Agricultural residues-to-grain weight and price ratios and multifactorial LCA allocations were summarized for the production stage. In addition, the energy use availability coefficient, collection radius, and emissions were determined for each fuel type during the collection stage. System boundaries and benefits of direct emissions reduction during the feedstock stage were also discussed. Our results provide guidance for future LCA studies on agricultural residue-based biofuels.